Citogenética comparativa de Physalis peruviana en tres poblaciones cultivadas de Cajamarca, Perú - Carbajal, Yajahaira (2021)
In this work, we characterized cytogenetically Physalis peruviana “aguaymanto” and cultivated populations of the Cajamarca region: San Pablo, Celendín and Cajabamba are compared. The most frequent chromosomal number in the three populations was 2n = 4x = 48 with frequencies of 60, 50 and 34% in San Pablo, Celendín and Cajabamba respectively. Few cases of somatic aneuploidy were found. Our results let distinguish the populations by its karyotypic formula 17m + 4sm + 3t, ​​24m and 20m + 2sm + 2t (San Pablo, Celendín and Cajabamba respectively). Karyotypes were characterized by the total length of the haploid complement (HCL) and the indices of symmetry (S%), asymmetry (A) and intra and interchromosomal asymmetry (A1 and A2). The highest value of HCL was described in San Pablo. Celendín presented the highest degree of symmetry (S% = 53.226 and A = 0.177), while the karyotypes of San Pablo and Cajabamba were described as the most asymmetric. We concluded that the tetraploidy is most frequent condition; although there is evidence of different chromosomal morphology between the three populations.